Characterization of the Nocardiopsin Biosynthetic Gene Cluster Reveals Similarities to and Differences from the Rapamycin and FK‐506 Pathways. Issue 6 (5th March 2015) - Bis, Dana M.; Ban, Yang H.; James, Elle D.; Alqahtani, Norah; Viswanathan, Rajesh; Lane, Amy L.
Abstract Macrolide‐pipecolate natural products, such as rapamycin (1) and FK‐506 (2), are renowned modulators of FK506‐binding proteins (FKBPs). The nocardiopsins, from Nocardiopsis sp. CMB‐M0232, are the newest members of this structural class. Here, the biosynthetic pathway for nocardiopsins A–D (4–7) is revealed by cloning, sequencing, and bioinformatic analyses of the nsn gene cluster. In vitro evaluation of recombinant NsnL revealed that this lysine cyclodeaminase catalyzes the conversion of L‐lysine into the L‐pipecolic acid incorporated into 4 and 5. Bioinformatic analyses supported the conjecture that a linear nocardiopsin precursor is equipped with the hydroxy group required for macrolide closure in a previously unobserved manner by employing a P450 epoxidase (NsnF) and limonene epoxide hydrolase homologue (NsnG). The nsn cluster also encodes candidates for tetrahydrofuran group biosynthesis. The nocardiopsin pathway provides opportunities for engineering of FKBP‐binding metabolites and for probing new enzymology in nature's polyketide tailoring arsenal.